ADVERSITY QUOTIENT OF SCHOOL ADMINISTRATOR AND THE TEACHER PROFESSIONAL STANDARDS PERFORMANCE NAKHONPATHOM PRIMARY EDUCATIONALSERVICE AREA OFFICE 2 - Ranechana , Panida; Tonwimonrat, Sakdipan (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of research were to determine 1) the administrator’s adversity quotient of schools under the Nakhonpathom Primary Educational Service Area Office 2 the teacher professional standards performance Nakhonpathom Primary Educational Service Area Office 2 and 3) the relationship between adversity quotient of school administrator and teacher professional standards performance Nakhonpathom Primary Educational Service Area Office 2. The sample used in this research consisted of informants from 86 educational institutions under the Nakhonpathom Primary Educational Service Area Office 2. The respondents from each school consisted of one school administrator and one teacher, in the total of 172 respondents. Complete questionnaires were obtained from 142 respondents representing 71 schools, accounting for 82.56 percent. The instrument employed for data collection was a opinionnaire about the administrator’s adversity quotient concept based on Stoltz and The implementation of professional teaching standards in educational institutions in accordance with the Teachers' Council of Thailand's Regulation on Professional Standards and Code of Ethics B.E. 2562 (2019). The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson' s Product Moment Correlation Coefficient. The research findings were as follows: 1) The administrator’s adversity quotient of schools under the the Nakhonpathom Primary Educational Service Area Office 2, as a whole and an individual, were at the highly level. 2) The teacher professional standards performance Nakhonpathom Primary Educational Service Area Office 2, as a whole and an individual, were at the highly level. 3) The relationship between adversity quotient of school administrator and teacher professional standards performance Nakhonpathom Primary Educational Service Area Office 2 were in a high correlation with a significance level at .01.